What do working menopausal women want? A qualitative investigation into women’s perspectives on employer and line manager support - Hardy, Claire; Griffiths, Amanda; Hunter, Myra S. (Elsevier, 2017)
Objectives: To explore women’s perspectives on what employers and managers should, and should not do in relation to women going through the menopause at work. Methods: An online questionnaire was used to collect qualitative data in a cross-sectional study of working women. Three open-ended questions asked peri- and post-menopausal women, aged 45-65 years: (i) what they thought employers could do, or should do, to help menopausal women who may be experiencing difficult menopausal symptoms at work; (ii) how managers should behave, and (iii) how managers should not behave towards women going through the menopause. Results: 137 women responded to the open questions in the survey. An inductive thematic analysis was conducted and three overarching themes emerged. Theme 1 related to employer/manager awareness, specifically to knowledge about the menopause and awareness of how the physical work environment might impact on menopausal women. Theme 2 related to employer/ manager communication skills and behaviors, specifically, those considered helpful and desired and those unhelpful and undesired. Theme 3 described employer actions, involving staff training and raising awareness, and supportive policies such as those relating to sickness absence and flexible working hours. Conclusions: The menopause can be difficult for some women to deal with at work partly due to the working environment. To our knowledge, this is the first study to explore women’s descriptions of how they would like to be treated by employers/managers, and what would be helpful and unhelpful. The results have clear implications for communication about menopause at work and for employer-level policy and practice.